Metodología para establecer una alianza estratégica hotelera en el municipio de San Agustín - Huila (2022)
The tourism and hotel sector has been one of the sectors most affected by the pandemic, which brought with it a great global economic crisis, due to the above, the objective of this work is to provide tools that help the gradual reactivation of the aforementioned sector, providing strategies through the approach of a hotel alliance proposal between the hotels: La Cumbre del Macizo, Adventure and El Cielo, in the municipality of San Agustín Huila, whose purpose is to potentiate the industry within the market, strengthen competitiveness and increase the demand.